Validitas Modul Pembelajaran Berbasis Constructivist Teaching Sequence (CTS) Berbantuan Augmented Reality (AR) Pada Materi Konsep Sel - Liytan, Elan Oktavia; Latjompoh, Masra; Mardin, Herinda; Zakaria , Zuliyanto; Usman, Nurul Fajryani (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2025)
This study aims to describe the validity of the Constructivist Teaching Sequence (CTS) learning module assisted by Augmented Reality (AR) on the cell concept material. The method used is Research and Development (R&D) with reference to the ADDIE development model which is implemented until the limited trial stage. This study uses a quantitative descriptive method which was implemented during July-December on 25 grade XI students of SMA Negeri 2 Gorontalo. The validation results show that the module obtained a score of 75% from material experts with the category